Exploração florestal certificada no cerrado: o crédito rural como mecanismo de fomento, controle e fiscalização - MARQUES, Carla Regina Silva (2010)
This search focuses on the Exploration of Wood in savanna, for certification, which aims to certify the origin of the product within the standards of sustainability. For this, some national and international methods have been decribed, as well as a brief description about the history and classification of Forest Certification. Secondly, the Rural Credit was exploited in its legal nuances and their applicability to logging. Finally, it was showed the possibility of logging in Savannah, in a sustainable way, when it was identified the main characteristics of this biome. In the end, it was concuded by the possibility of histype of agriculture activity in Savanna, to wich it can be used several lines of financing offered by financial institutions. From the legal point of view, highlighted the bias developer of Agricultural Law, in contrast to the bias sanctions Environmental Law.